Pengaruh Literasi Digital, Promosi, Citra Merek, dan Kepercayaan Terhadap Keputusan Mahasiswa STIE Pancasetia Menggunakan Bank Digital - Nico Kosasih; Rika Yuliyanti; Aulia Helmina Putri (eCo-Fin, 2025)
According to a report by Bank Indonesia, in the third quarter of 2023, e-money usage increased by 10.34% year-on-year, reaching IDR 116.54 trillion. Meanwhile, digital banking transactions grew by 12.83% year-on-year, amounting to IDR 15,148.71 trillion. One of the key factors driving the rise of digital banking is the behavior of millennials, who are accustomed to the ease and convenience of mobile transactions. This study aims to investigate the influence of digital literacy, promotion, brand image, and trust on the decision of STIE Pancasetia students to use digital banking services. This quantitative research involved a sample of 100 STIE Pancasetia students. The sampling technique applied was non-probability purposive sampling, requiring participants to be students of STIE Pancasetia who are also users of digital banking services. Data analysis was conducted using multiple linear regression, with hypothesis testing performed through F-tests and t-tests. The results indicated that promotion, trust, and brand image each have a significant partial effect on the decision to use digital banking.